2017
DOI: 10.3390/beverages3040047
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to a Low-Fat Milk Social Media Intervention in the US: The Choose 1% Milk Campaign

Abstract: (1) Background: Social media has increased in importance as a primary source of health communication but has received little academic attention. The purpose of this study was to conduct a content analysis of Facebook comments made in response to a five-week statewide social media intervention promoting use of 1% low-fat milk. Formative research identified health messages to promote, and 16 health messages consistent with the Dietary Guidelines for Americans were posted. During the intervention, 454 Facebook us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Segmentation is a key criterion underlying social marketing which involves dividing the target population into smaller groups or segments and tailoring the marketing activities and materials to meet the specific needs of the segments (Andreasen, 2002). All the interventions analysed defined specific target audiences, however, only 14 studies reported using segmentation with 12 reporting positive behavioural outcomes (Adam et al, 2016;Bopp et al, 2018;Cates et al, 2014;Cates et al, 2018;Evans et al, 2016;George et al, 2016;John et al, 2017;Loh et al, 2018;Rundle-Thiele et al, 2015;Shah et al, 2020;Tait et al, 2019;Yam et al, 2017). Yam et al (2017) segmented based on the size of the user's energy bill ("Whatevers", "Breaking Even", "Help me").…”
Section: Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Segmentation is a key criterion underlying social marketing which involves dividing the target population into smaller groups or segments and tailoring the marketing activities and materials to meet the specific needs of the segments (Andreasen, 2002). All the interventions analysed defined specific target audiences, however, only 14 studies reported using segmentation with 12 reporting positive behavioural outcomes (Adam et al, 2016;Bopp et al, 2018;Cates et al, 2014;Cates et al, 2018;Evans et al, 2016;George et al, 2016;John et al, 2017;Loh et al, 2018;Rundle-Thiele et al, 2015;Shah et al, 2020;Tait et al, 2019;Yam et al, 2017). Yam et al (2017) segmented based on the size of the user's energy bill ("Whatevers", "Breaking Even", "Help me").…”
Section: Segmentationmentioning
confidence: 99%
“…As Loh et al (2018) developed a multi-level intervention and engaged with multiple stakeholders, had different aims and messages for the multiple stakeholders involved. Seven interventions adapted their materials into at least one other language: English and Spanish (Rogers et al, 2017;John et al, 2017;George et al, 2016;Cates et al, 2014;Cates et al, 2018), English, French and Arabic (Evans et al, 2016) and English and French (Adam et al, 2016).…”
Section: Segmentationmentioning
confidence: 99%
“…Because of the flexibility of social media, a targeted advertisement post addressed this specific misperception. A content analysis of the positive and negative audience reactions to the Facebook posts is available elsewhere (John, Finnell, Kerby, Owen, & Hansen, 2017).…”
Section: Implementation: Choose 1% Milkmentioning
confidence: 99%
“…Several of the scientists that contributed to this Special Issue investigated and tested the effectiveness of actions targeting the promotion of milk, and an increase in general daily milk consumption, especially for children: an important goal to achieve [1][2][3][4]. Gennaro et al [3] provide an updated picture of communication strategies developed to improve healthy dietary habits in schoolchildren, with a focus on the importance of milk consumption.…”
Section: Introductionmentioning
confidence: 99%
“…An example of this strategy is given by Emerson et al [1]: small prizes increased plain milk and vegetable selection by elementary schoolchildren without adversely affecting total milk purchase. Two [2,4] of these studies are addressed towards consumer reactions relating to interventions promoting use of 1% low-fat milk.…”
Section: Introductionmentioning
confidence: 99%